THE RELATIONSHIP OF LONELINESS AND SOCIAL SUPPORT IN INFERTILE COUPLES - Khoshbin, A; Roshaninegad, M; Molahoseini, SH; Haghani, H (Iran University of Medical Sciences, 2001)
Background : Most of infertile couples experience loneliness, which is intensified with inappropriate response of others. Loneliness is not only an unpleasant feeling, but it is associated with variety of somatic complaints and psychological distress. Most studies have shown that social support reduces psychological distress and has inverse relation with loneliness.   Objective : To determine relationship between loneliness and social support in infertile couples.   Design : This was a correlational study in which loneliness and social support were measured. Then the relationship between these two variable were determined in wives and husbands.   Samples : For the purpose of this study 70 couples with primary infertility were selected through consecutive sampling method.   Results : The findings showed a signigcant relation between perceived social support and loneliness in wives (r = -70% P<0.001) and husband (r = -67%, P<0.001).   Conclusion : Based on the study's findings, as social support increased, loneliness decreased. There for promotion of perceived social support in infertile couples, are important. Having intimate relationship with infertile couples are recommended.